Halal Tourism's Economic Effects: Accounting-Governance Framework for Emerging Markets - Harmin Darwis; Muryani Arsal; Zulkifli (www.amertainstitute.com, 2025)
The purpose of this study is to evaluate the economic impact of halal tourism through the integration of accounting and governance frameworks. Using a Systematic Literature Review (SLR) approach, the research synthesizes peer-reviewed literature across tourism, accounting, and governance to identify prevailing gaps in financial measurement and policy alignment. The methodology involved rigorous selection criteria, thematic coding, and structured content analysis of recent open-access academic publications. The results show that while the halal tourism sector has expanded significantly, it lacks frameworks for economic accountability and measurable governance outcomes. The study implies that integrating sharia-compliant accounting and institutional governance can improve transparency and policy effectiveness in halal tourism. The novelty of this research lies in its proposed conceptual model that bridges disciplinary boundaries, providing a foundational framework for future empirical validation.